The Write Around as a Useful Strategy to Improve Students’ Writing Skill of Report Text - Herlisya, Destia; Sutiyono, Akhmad (Lentera: Jurnal Ilmiah Kependidikan, 2024)
Since was in school, the high schoolers need to be mastered English writing skill, because in senior high school there are kind of texts that they need to learn. That is why the ability to write English texts is very important also for university students especially for those studying in the economics education. The Problems in writing that students faced is not only in generating ideas but also in arranging the sentences. The students have difficulty in distinguishing which are noun, adverb, adjective and verb. The students have low score because there are many mistakes in their writing. The objective of this research is to raise the students’ skill in writing report text through write around strategy. The write around strategy can increase students’ motivation in writing and allow them to be more enjoy in writing activity. Through write around strategy, it makes easier for the students to compose sentences and express their mind into the writing form. The subject of the research were the third semester students in economic education of STKIP PGRI Bandar Lampung in the academic year 2023/2024. The questions in this research are, whether employing the write around strategy can improve students’ learning activity in writing and whether employing the write around strategy can improve students’ writing skill of report text. In this research, a second-cycle classroom action research design was adopted as the methodology. Keywords: Write Around Strategy, Classroom Action Research, English Writing